Cardiac Resynchronization Therapy With or Without Defibrillation in Patients With Nonischemic Cardiomyopathy: A Systematic Review and Meta-Analysis. (17th May 2021) - Patel, Divyang; Kumar, Anirudh; Black-Maier, Eric; Morgan, Rebecca L.; Trulock, Kevin; Wilner, Bryan; Nemer, David; Donnellan, Eoin; Tarakji, Khaldoun G.; Cantillon, Daniel J.; Varma, Niraj; Saba, Samir F.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Cardiac resynchronization therapy (CRT) represents a major medical advance in patients with heart failure with electrical dyssynchrony to improve symptoms, reduce hospitalization, and increase survival both in the presence and absence of implantable cardioverter-defibrillator therapy. However, among CRT-eligible patients with nonischemic cardiomyopathy (NICM), the benefit of defibrillator therapy in addition to CRT remains unclear. A systematic review and meta-analysis comparing outcomes of patients with NICM and heart failure who underwent CRT with implantable cardioverter-defibrillator (CRT-D) versus CRT-pacemaker only (CRT-P) was, therefore, performed. Methods: A literature search from inception through February 2020 was conducted in PubMed and Cochrane Review Databases for all studies reporting outcomes of CRT-D versus CRT-P in CRT-eligible patients with NICM. Studies reporting nonstratified outcomes, including patients with ischemic cardiomyopathy, were excluded. The primary end point of interest was all-cause mortality. A random-effects model using hazards ratio (HR) was used to calculate a cumulative HR for all-cause mortality. The Grading of Recommendations Assessment, Development, and Evaluation approach assessed the certainty of evidence across outcomes. Results: Of a total of 1478 potential citations, the search yielded 8 citations that met inclusion and exclusion criteria. There was one randomized controlled trial which included a subgroup of 645 CRT-eligible patients with NICM (322 with CRT-D and 323 with CRT-P). Seven observational studies representing 9944 CRT-eligible patients with NICM (6865 CRT-D implantation and 3079 with CRT-P) were included in a pooled meta-analysis. The cumulative adjusted HR for all-cause mortality for CRT-D versus CRT-P was 0.92 (95% CI, 0.83–1.03); I 2 =0 though with low certainty of evidence. There may be little difference in infection and cardiac mortality between CRT-D versus CRT-P devices (HR, 0.82 [95% CI, 0.29–2.20] moderate certainty of evidence and HR, 0.68 [95% CI, 0.37–1.25], low certainty of evidence, respectively). Conclusions: In this meta-analysis, the addition of defibrillator therapy was not significantly associated with a reduction in all-cause mortality in CRT-eligible patients with NICM.